Attention deficit hyperactivity disorder and sleep disordered breathing in children - Sedky, Karim; Nazir, Racha; Carvalho, Karen S.; Lippmann, Steven (Journal of Pediatric Biochemistry, 2013)
Children and adolescents suffering from attention deficit hyperactivity disorder (ADHD) and/or sleep disordered breathing (SDB) may present with similar symptoms, including inattention, irritability, and hyperactivity. SDB is under-diagnosed in young people and is not often recognized in patients with ADHD; we hypothesize that treating sleep disordered breathing in ADHD patients may diminish symptoms and reduce ADHD-focused pharmacotherapy. A Medline search was performed using the criteria for ADHD and SDB. English language publications through January, 2012 were surveyed. Correlation between these two disorders is confounded due to methodological errors in research. The investigations lack consistency due to studies with small sample size, a dearth of diagnostic polysomnography (PSG) to detect SDB, varying definitions for the apnea/hypopnea index, and lack of uniform evaluations to diagnose ADHD. Despite methodological inconsistencies, the data suggests that treating SDB may have a productive impact on treatment outcomes in children with mild ADHD. Patients with ADHD symptomatology should receive SDB screening. In those with comorbid SDB and ADHD, an adenotonsillectomy (AT) may improve the prognosis. Treatment of SDB coexisting with ADHD aims to decrease clinical symptoms, reduce pharmacotherapy, and promote better health.
Keywords: Attention deficit hyperactivity disorder; ADHD; sleep disordered breathing; SDB; obstructive sleep apnea; OSA